1999
DOI: 10.1038/sj.cdd.4400575
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-15 is a potent survival factor in the prevention of spontaneous but not CD95-induced apoptosis in CD4 and CD8 T lymphocytes of HIV-infected individuals. Correlation with its ability to increase BCL-2 expression

Abstract: IL-15 shares many biological properties with IL-2, a cytokine whose administration to HIV-infected individuals has been effective in enhancing depleted CD4 T lymphocyte numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…46,48,49,102,[116][117][118][119][120][121][122] Thus, the addition of antibodies to IL-10 or the addition of IL-12 have a preventive effect on abnormal programmed cell death induction in response to in vitro stimulation in HIV-infected persons. 46,48 Moreover, we found that IL-12, which upregulates TH1 functions and prevents TCR-mediated CD4 T-cell apoptosis, also prevents Fas-mediated apoptosis of CD4 þ T cells from HIV-infected persons.…”
Section: Preventive Effect Of Cytokinesmentioning
confidence: 99%
“…46,48,49,102,[116][117][118][119][120][121][122] Thus, the addition of antibodies to IL-10 or the addition of IL-12 have a preventive effect on abnormal programmed cell death induction in response to in vitro stimulation in HIV-infected persons. 46,48 Moreover, we found that IL-12, which upregulates TH1 functions and prevents TCR-mediated CD4 T-cell apoptosis, also prevents Fas-mediated apoptosis of CD4 þ T cells from HIV-infected persons.…”
Section: Preventive Effect Of Cytokinesmentioning
confidence: 99%
“…ACAD is normally prevented by cytokines and, accordingly, IL-2 and IL-15 can promote in vitro the survival of patients' T cells by upregulating the expression of Bcl-2. 97,98 As discussed below, immunotherapy with these cytokines are actually under evaluation to restore HIV-specific immunity.…”
Section: Activated T-cell Autonomous Deathmentioning
confidence: 99%
“…140 Altered differentiation of CTL might also be linked to an unfavorable cytokine environment, as rescue from apoptosis of the Bcl-2 low CD8 T cell subset, detected in the lymph nodes and blood of individuals chronically infected with HIV, can be induced by exogenous IL-2 and IL-15. 95,97,98 Defective help CD4 þ T cells are the helper cells (T h ) of the immune system that facilitate the generation of antibody and CTL responses. After encountering the antigen, naive T h cells can differentiate into at least two functional classes of cells during an immune response -T h 1 cells, which secrete IFN-g, and T h 2 cells, which secrete IL-4.…”
Section: Impairment Of Hiv-specific Cd8 T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…131 On the other hand, in vitro treatment with IL-2 corrects the cell-cycle deregulation observed in CD8 þ T cells from HIV-positive patients, indicating a role of cytokine deficiency in apoptosis of CD8 þ T cells. 132 Exogenous cytokines like IL-2, IL-10, IL-12 and IL-15 can inhibit apoptosis of CD8 þ T cells in vitro [133][134][135][136] and augment in vitro the immune functions of peripheral blood mononuclear cells (PBMCs) from HIV-infected patients, 137 further supporting the involvement of cytokines in the CD8 þ T-cell loss in HIV infection. An altered cytokine profile toward a Th2 type (IL-4, IL-5, IL-6, IL-10) has been suggested; 138 however, this has been challenged in other studies where an intracellular staining assay was used to determine cytokine production in HIV-infected patients.…”
Section: Role Of Cytokine Milieu In Hiv-specific Cd8 þ T-cell Apoptosismentioning
confidence: 98%